1974
DOI: 10.1190/1.1486795
|View full text |Cite
|
Sign up to set email alerts
|

Reply by author to discussion by Dr. S. K. Singh

Abstract: Dr. Singh rightly points out that in this paper the transient response was obtained through the inversion of the already available frequency response (Wait, 1952). The neglect of the monopolar contribution ([Formula: see text] term) by Dr. Wait remained unnoticed, rather surprisingly, for well over two decades! The results obtained in my paper would, therefore, appear to be misleading, or more appropriately, incomplete. There are some significant factors, however, which reveal that the apparent fallacy in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 0 publications
3
38
0
Order By: Relevance
“…It has been experienced by us 18 and Professor Hogarth's coworkers 19 that transition metal dithiocarbamate complexes with functionalised backbones are easy to synthesize but their crystallization can be more problematic. L and 1-5 were characterized by microanalysis, standard spectroscopy viz.…”
Section: -Chloro-3-{2-(piperazinyl)ethyl}-amino-14-naphthoquinone (L)mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been experienced by us 18 and Professor Hogarth's coworkers 19 that transition metal dithiocarbamate complexes with functionalised backbones are easy to synthesize but their crystallization can be more problematic. L and 1-5 were characterized by microanalysis, standard spectroscopy viz.…”
Section: -Chloro-3-{2-(piperazinyl)ethyl}-amino-14-naphthoquinone (L)mentioning
confidence: 99%
“…A new band clearly seen at 389 nm in the electronic absorption spectrum of nickel complex 3, probably arises due to intra ligand charge transfer transitions associated with N-C]S group of coordinated dithiocarbamate ligands. 18,27 The Zn(II) complex 5 is of white colour and presents a featureless electronic spectrum. Further, cobalt(III) complex 2 exhibits a weak absorption band at $649 nm, which is consistent with the absorption behavior of [Co{k 2 S,S-S 2 C-piperazine-C 2 H 4 N]C(Ph)} 3 ] 18 and other cobalt(III) complexes.…”
Section: Electronic Absorption Spectral and Magnetic Moment Studiesmentioning
confidence: 99%
“…The peaks corresponding to the ligand functionalities in the 1 H NMR spectra of the complexes (Supporting Information) appear very well in the expected range. Distinctly, in the 13 C NMR spectra, all the diamagnetic complexes showed a single distinct downfield resonance at δ 206–207 ppm associated with the N–CS 2 unit ,. (Figure S12, S14, S16, S18, S20, S22).…”
Section: Resultsmentioning
confidence: 96%
“…In our study, chitogallates also have antioxidants activities as well as GA itself as shown in Figure . Many reports noted that natural materials having antioxidant power are able to suppress MMP activities in cancer cells and, then, reduce invasion, metastasis and angiogenesis of tumor . Antioxidants potential is related to suppress MMP activities and inhibition of MMP has an important to inhibit invasion/metastasis of cancer cells .…”
Section: Discussionmentioning
confidence: 99%